Knowledge of Kratom among Alabama Pharmacists - Scott R. Penzak; Spencer H. Durham; Haley M. Phillippe; Brent I. Fox (MDPI AG, 2023)
Kratom (Mitragyna speciosa) is a botanical substance whose leaves produce stimulant- and opioid-like effects. Kratom use has increased precipitously in the United States (U.S.) over the last decade, yet, in our experience, many pharmacists are unfamiliar with this herb. The purpose of this study was to assess pharmacists' awareness and knowledge of kratom. This cross-sectional study used an online questionnaire to preferentially solicit community pharmacists' knowledge of kratom and collect demographic information. The survey was sent via email to approximately 10,000 pharmacists, targeting those in the state of Alabama, U.S. Data were analyzed using descriptive statistics, and the Chi Square test was used to compare nominal data. A total of 257 participants responded to the survey. Almost 50% of participants had heard of kratom, and 50% had not. Compared to females, males were more likely to have heard of kratom (64% vs. 42%; p = 0.0015), as were pharmacists who worked for an independent pharmacy vs. a chain (61% vs. 41%; p = 0.025). Of the participants who had heard of kratom, only 14% considered themselves knowledgeable or very knowledgeable about the herb, and only 44% knew it was illegal in Alabama. These data indicate a need to further kratom education among community pharmacists in Alabama.